Factors Affecting the Income of Labor Fishermen (Case Study: Tebing Tinggi Village, Tanjung Beringin District, Serdang Bedagai Regency) - Rizal Aziz; Roni Paulus Sihombing; Rahma Sari Siregar; Saipul Sihotang (Postgraduate, University of Mataram, 2023)
Indonesia is a country that has a very large water area which is a large potential resource to be utilized for national development. This condition affects the strong weak economic activities of the village. The purpose of the study is to find out how much the income of labor fishermen in Tebing Tinggi Village, Tanjung Beringin District, Serdang Bedagai Regency and to find out what factors affect the income of labor fishermen in Tebing Tinggi Village, Tanjung Beringin District, Serdang Bedagai Regency. This research was conducted in Tebing Tinggi Village, Tanjung Beringin District, Serdang Bedagai Regency, North Sumatra Province. This location was chosen intentionally (Purposive). The population in this study was 546 labor fishermen, the determination of the sample in this study used Arikunto's theory, namely if the total population was less than 100 people, then the number of samples was taken as a whole. But if the population is larger than 100 people then it can be taken 10-15% and 20-25% of the total population. The samples in this study were taken as much as 10% of the total population, so the number of samples in this study was 55 labor fishermen. Data collection techniques use primary data and secondary data, data analysis techniques in research use income analysis and multiple linear regression analysis. The results of the research on the working capital costs of labor fishermen amounted to Rp. 244,894/month, with an income of Rp. 4,128,386/month with an average of 12 trips a month of fishing. The results of multiple linear regressions that the working capital variable and the catch variable have a significant effect on the income of labor fishermen while the time variable at sea and experience variables do not have a significant effect on the income of labor fishermen in Tebing Tinggi Village, Tanjung Beringin District, Serdang Bedagai Regency.